Pheidole & Odontomachus (Hymenoptera: Formicidae): predadoras ou dispersoras de sementes? - Pereira, Guilherme Andrade (Universidade Federal de São Carlos, 2024)
Despite being known as predators of arthropods, many species of ants use fruits and seeds as food, transporting them to their nests. Part of the seeds can be discarded in a midden near the entrance or inside the nest after the fruit pulp or the aril that covers the seed is consumed. Some of these seeds may still be viable and potentially germinate. Through this behavior, ants can disperse seeds of species without apparent adaptation to dispersal by ants and contribute to plant regeneration. We evaluated the capacity of seed removal by ants and the germination of seeds that interacted with Pheidole and Odontomachus, which are abundant ants in many Neotropical ecosystems and commonly interact with fruits/seeds. We investigated how seed attributes, such as size, shape and presence of a reward (pulp or aril), can influence the chance of seeds being removed. Artificial nests of these ants were kept in the lab, where seeds of different types and shapes were offered as food. It was possible to confirm the seed removal and dispersal capacity of both ants. However, Odontomachus performed better in this task, probably due to its size and foraging method. In general, seed germination was not altered by contact with ants in any case, implying that both ants are indeed seed dispersers. The exception was the interaction between Pheidole and Solanum viarum, in which the ant clearly behaves as a granivore rather than a seed disperser.
Pheidole & Odontomachus (Hymenoptera: Formicidae): seed predators or dispersers?
Keywords: Interações Planta-animal; Plant-animal Interactions; Regeneração de Plantas; Plant Regeneration; Germinação; Seed Germination; Cerrado; Floresta Estacional Semidecídua; Seasonal Tropical Forest; CIENCIAS BIOLOGICAS::BOTANICA::BOTANICA APLICADA; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS BIOLOGICAS::ZOOLOGIA